(untitled) (Saúde Ética & Justiça, 2004)
The authors presents the case of a five years old child that was murdered by hands strangled and also she had signs of physical and sexual abuse. The difficulty of characterizing the sexual violence, if was rape or sexual abuse otherwise copulation, was diagnosing sexual intercourse. The medical literature indicates that the hymenal characteristics are the essencial element for this diagnose. However, the hymenal rupture, recent or not, like certain sign would be controversial if accidental trauma occurred in the perineum.